Gambaran Hasil Pemeriksaan IMLTD Reaktif Metode CHLIA pada Kasus Reaktif HBsAg dan HCV di UDD PMI Kota Surakarta Tahun 2021 - Nur Alifah Dina Safitri; Ni'mah Hidayatul Laili (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Hepatitis B is a liver disease caused by the Hepatitis B virus which can cause acute liver inflammation. Hepatitis C is one of the viruses that can cause infection in liver cells that can be transmitted through the blood. To describe the results of the CHLIA ??reactive IMLTD examination in reactive HBsAg and HCV cases at UDD PMI Surakarta in 2021. HBsAg reactive in 2021 with the CHLIA ??167 method, based on the time period of March, April, August 20 (12.0%), based on the age range of 25 – 44 years 78 (46.7%), based on male sex 131 ( 78.4%), based on blood type O 67 (40.1%). Reactive HCV in 2021 CHLIA ??method 30 , based on time period March 6 (20.0%), based on age range 25 – 44 years 15 (50.0%), based on male sex 27 (90.0%), based on blood group blood group B 14 (46.7%).